Pengaruh Profitabilitas Pada Nilai Perusahaan dengan Corporate Social Responsibility Sebagai Variabel Moderasi - Dewi Ariasih, Ni Putu; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2018)
The purpose of this study is to analyze the effect of profitability on corporate value with Corporate Social Responsibility as a moderation variable. This research was conducted at the Manufacturing company registered by BEI in 2014-2016. The sampling method used is purposive sampling. Number of companies that meet the criteria is 78 companies that have related data mengai variables used. Data collection was done by non participant observation method. Technique Data analysis used is test of Moderated Regression Analysis (MRA). Based on the result of research, show that profitability have a significant positive effect to company value, Corporate Social Responsibility able to moderate the influence of profitability at company value. The study also found that Corporate Social Responsibility weakens the effect of profitability on corporate value. Keywords: Profitability, Corporate Value, Corporate Social Responsibility